Post-procedure anticoagulation in patients with acute ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. (14th October 2021) - Yan, Y; Gong, W; Ma, C; Wang, X; Smith Jr, S C; Fonarow, G; Morgan, L; Liu, J; Vicaut, E; Zhao, D; Montalescot, G; Nie, S; et al.
Abstract: Background: Post-procedural anticoagulation (PPAC) after primary percutaneous coronary intervention (pPCI) in patient with ST-segment elevation myocardial infarction (STEMI) may prevent recurrent ischemic events but may increase the risk of bleeding. No consensus has been reached on PPAC use. Methods: Using data from the CCC-ACS registry, conducted between 2014 and 2019, we stratified all STEMI patients who underwent pPCI according to the use of PPAC or not. Inverse probability of treatment weighting (IPTW) and Cox proportional hazards model with hospital as random effect were used to analyze differences in in-hospital clinical outcomes: the primary efficacy endpoint was mortality, and the primary safety endpoint was major bleeding. Results: Of 34, 826 evaluable patients 26, 272 (75.4%) were treated with PPAC, and were on average younger, more stable at admission with lower bleeding risk score, more likely to have comorbidities and multivessel disease, and more often treated within 12 hours of symptom onset than those without PPAC. After IPTW adjustment for baseline differences, PPAC was associated with significantly reduced risk of in-hospital mortality (0.9% vs. 1.8%; hazard ratio (HR): 0.62 [95% confidence interval 0.43, 0.89]; p<0.001) and a nonsignificant difference in risk of in-hospital major bleeding (2.5% vs. 2.2%; HR: 1.05 [0.83, 1.32]; p=0.14). Conclusions: PPAC in STEMI patients after pPCI was associated with reduced mortality without increasing major bleeding complications. Dedicated randomized trials with contemporary STEMI management are needed to confirm these findings. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The Improving Care for Cardiovascular Disease in China – Acute Coronary Syndrome (CCC-ACS) project is a collaborative study of the American Heart Association (AHA) and the Chinese Society of Cardiology (CSC). The AHA has been funded by Pfizer and AstraZeneca for quality improvement initiatives through an independent grant.